Modelling and Simulation of Refrigerated LPG Recovery System at Lysekil Refinery - PREEM AB, Sweden - Raja, Arsalan Ahmad (My University, 2009)
Big process industries like PREEM AB, Sweden refining 16 million tonnes of crude oil annually are investigating the black boxes at their site to cut down unnecessary power consumption. This project study initiated by PREEM Lysekil Refinery is an example, to investigate the output i.e., recovery of LPG (propane and butane) in comparison to the power input to the refrigeration section. In oil refineries, it is always interesting to recover valuable products like liquefied petroleum gas – LPG from the refinery streams. An analysis has been conducted at the refrigerated LPG Recovery Unit by modelling and simulating the unit in an advanced process engineering tools, ASPEN HYSYS assisted by ASPEN HTFS+ an energy equipment calculation tool, to investigate the performance and possibilities in the current system. Despite the engineering challenges to model the unique refrigerated LPG recovery system in HYSYS, the system was simulated to analyse the current operation. The simulation concluded that the lean off-gas stream, one out of three, was only cooled but not condensed. This imposed an extra load in the refrigeration cycle only used to extract specific heat from the off-gas stream instead of recovering LPG. Such findings led to investigation of the refrigeration load and LPG recovery only for off-gas streams, rich in propane and butane. 657 kg/h of LPG was recovered from 1078 kg/h of incoming off-gas stream with 25% reduction in refrigeration power consumption. A minor retrofit for exchanging heat between recovered LPG and incoming rich off-gas stream proved to save comparatively more power, i.e., 37%, with the same LPG recovery in the refrigerated LPG recovery system in the HYSYS model. The simulated model predicts that the present unit is capable of handling another rich off-gas stream of a size similar to the lean off-gas stream (2814kg/h), which is proposed to be removed. The introduction of the new rich off-gas stream will lead to more LPG recovery, in an efficient way, at the expense of slightly increased power consumption, due to high dew. Recovering more LPG leads to fuel gas deficiency and that would be compensated by introducing cheaper fuels like natural gas from Norway, included in the strategic planning of the refinery. Another project could be conducted to thoroughly analyse the impact of more LPG recovery, from new rich off-gas stream, on the refrigeration load.
Keywords: Miljökemi; Kemiteknik; Environmental chemistry; Chemical Engineering